Case Report: Chronic subdural hematoma secondary to primary central nervous system lymphoma - Mu, Xinli; Song, Zhihui; Wang, Qihong; Yue, Hongsheng; He, Xin (Frontiers in Surgery, 2025)
A 69-year-old man presented with a 15-day history of right-sided motor impairment and slurred speech. Twenty-one days earlier, he was misdiagnosed at a local hospital with a routine chronic subdural hematoma (CSDH) and underwent burr-hole drainage, but his symptoms progressively worsened postoperatively, leading to aphasia and prompting his admission to our hospital. Further MRI and contrast-enhanced imaging revealed hematoma organization, brain herniation, and an intracranial mass lesion. The patient underwent craniotomy for tumor resection and evacuation of the organized hematoma. The patient received structured rehabilitation and limb positioning therapy during hospitalization to support motor recovery and prevent complications, and was discharged on postoperative day 13 with improved limb function but persistent aphasia. Histopathological analysis confirmed non-germinal center diffuse large B-cell lymphoma (DLBCL) within the hematoma, supported by immunohistochemical and FISH findings, including CD20(+), PAX-5(+), MUM-1(+), and Ki-67(+, 60%). The patient underwent four cycles of rituximab and high-dose methotrexate, resulting in lesion resolution on follow-up MRI, with motor aphasia persisting. This case represents a rare instance of primary central nervous system lymphoma (PCNSL) initially presenting as CSDH, with progression to hematoma organization and brain herniation. This case provides new insights and experience in recognizing and managing rare clinical presentations of primary central nervous system lymphoma.